2010
DOI: 10.1007/s12274-010-0016-6
|View full text |Cite
|
Sign up to set email alerts
|

One-pot polymerase chain reaction with gold nanoparticles for rapid and ultrasensitive DNA detection

Abstract: We report a novel method for rapid, colorimetric detection of a specific deoxyribonucleic acid (DNA) sequence by carrying out a polymerase chain reaction in the presence of gold nanoparticles functionalized with two primers. Extension of the primers when the target DNA is present as a template during the polymerase chain reaction process affords the complementary sequences on the gold nanoparticle surfaces and results in the formation of gold nanoparticle aggregates with a concomitant color change from red to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…2018, 11(10): 5439-5473 Plasmonic NPs with vivid colors have been used as colorimetric labels for PCR, which eliminate the need of more expensive, less stable fluorescent dyes, and therefore enable rapid quantification of PCR results without the need of complex optical instrumentation. Wang et al reported a colorimetric PCR assay where Au NPs were conjugated directly to the primers [117]. As shown in Fig.…”
Section: Plasmonics-enhanced Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…2018, 11(10): 5439-5473 Plasmonic NPs with vivid colors have been used as colorimetric labels for PCR, which eliminate the need of more expensive, less stable fluorescent dyes, and therefore enable rapid quantification of PCR results without the need of complex optical instrumentation. Wang et al reported a colorimetric PCR assay where Au NPs were conjugated directly to the primers [117]. As shown in Fig.…”
Section: Plasmonics-enhanced Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Specifically, particle aggregation gives rise to a red shift of the SPR absorption band and a concomitant red‐to‐purple color change. This property has been utilized for solution‐phase colorimetric detection of specific nucleic acid sequences . Nevertheless, these previously reported detection platforms did not possess all the essential attributes needed for practical applications, including high sensitivity, simple temperature control, no carryover contamination, and low cost.…”
mentioning
confidence: 99%
“…Pioneer studies regarding the modification of gold NPs with oligonucleotides were reported way back in 1996 (Alivastos et al 1996; Mirkin et al 1996, as cited in [12]) and a number of studies have been reported since then concerning gold NP-oligonucleotide conjugate systems aimed at detection of complementary DNA sequences [13][14][15][16]. While gold NPs have been in prime focus, only a few reports are available for silver NPs in such systems.…”
Section: Nanoparticles In Diagnosismentioning
confidence: 99%